Factors Influencing Litigation Compensation in Plastic Surgery: A Retrospective Analysis in China - Xueshang Su, MD; Yutong Liang, MD; Jun Zhuang, MD; Qingqian Wei, MD; Ziming Zhang, MD; Xue Ouyang, MD; Haixia Jiang, MD; Na Cai, MD; Jintian Hu, MD; Bo Ding, MD (Plastic and Reconstructive Surgery, Global Open)
Background:. Doctor–patient disputes have become a prominent problem in contemporary society. The analysis and discussion of the factors leading to litigation compensation are essential to prevent and resolve doctor–patient conflicts, reduce litigation events, and provide better service for patients. Methods:. We reviewed the medical lawsuit cases of a plastic surgery hospital over the past 8 years. After excluding 11 withdrawal cases, we analyzed the types of surgery, surgical sites, and causes of litigation compensation in the remaining 36 cases. Subsequently, we proposed preventive measures to avert similar occurrences. Results:. Thirty six medical malpractice lawsuits were filed, 23 of which involved cosmetic surgery. In 72.2% (26 of 36) of the cases, disputes were resolved through compensation, with the majority involving facial plastic surgery, including procedures on the skin, eyes, nose, forehead, ears, and jaw. The primary reasons for pursuing legal action included dissatisfaction with surgical outcomes, postoperative complications or disabilities, lack of informed consent, inadequate doctor–patient communication, and insufficient preoperative examination records. Additional factors included improper medical documentation, deviation from established medical protocols, noncompliance with surgical indications, and insufficient attention to patient needs. Furthermore, 1 lawsuit was filed due to an incident in which a patient’s family member fell on hospital stairs. Conclusions:. Plastic surgery often leads to lawsuits because patients are not satisfied with the cosmetic results. In reconstructive surgery, the causes of litigation are mainly postoperative complications, mainly infections. Doctor–patient communication remains the most important issue, especially effective and active communication.